Pembuatan Alat Pengukur Arus Bernilai Micro Menggunakan Resistor Shunt Dan Modul Op-Amp AD620 - Hastia Ningsih M. Nur; Paris Ali Topan; Titi Andriani; Ahmad Jaya (Program Studi Teknik Elektro, 2023)
Current measuring device is still on the unit ampere and milliampere not yet on the unit micro amperage. Therefore, made a measuring instrument that can measure small currents in micro amperage. The purpose of this study is to find out how to measure current using a resistor shunt and the AD620 module on the unit microampere. The method used is the experimental method which includes: the tool design stage, the testing stage, and the data collection stage. There are 2 tool design stages, namely the first stage is the design stage for testing the MCP4725 module and the AD620 module, the second is the current measurement design stage. Test results of current measurements by varying the resistor from 10 k?-100k? to obtain different current values. When it is installed with a 10 k? resistor, it gets a current value of 0.00103 µA and when it is installed with a 20 k? resistor, it gets a current value of 0.00093. It can be seen that the greater the resistance value, the smaller the required current value and vice versa.